On Weighted Possibilistic Mean, Variance and Correlation of Interval-Valued Fuzzy Numbers (Communications in Mathematical Research, 2021)
In this paper, the concept of weighted possibilistic mean of interval-valued fuzzy number is first introduced. Further, the notions of weighted possibilisticvariance, covariance and correlation of interval-valued fuzzy numbers are presented.Meantime, some important properties of them and relationships between them arestudied.
Keywords: Interval-valued fuzzy number; weighted possibilistic mean; weighted possibilistic variance; weighted possibilistic correlation.